Modern theory and practice of concrete technology for 3D printing in construction - A. S. Inozemtcev (Vestnik MGSU)
Introduction. The analysis of scientific works devoted to the development and research of building materials, products and structures in 3D printing technology was carried out in this work. The purpose of the research is to identify actual development trends, current advantages and disadvantages based on an analysis of international theoretical and practical experience in the manufacture of products and structures, achieved properties of materials, used quality criteria and methods for their evaluation.Materials and methods. The complex of general scientific logical methods of research based on theoretical analysis of technological solutions presented in scientific and technical literature, information resources from developers and media recourses, including patents, scientific articles and scientific reports are used in this paper.Results. The key issues that need to be addressed for the development of 3D printing are related to mixture workability, deformation and extruded layer strength. There are many examples of ink compositions for 3D printers of various devices with high performance. The average composition of concrete for 3D printing contains binder, aggregate, water and mineral additives, plasticizer and reinforcing fibres. Large-scale implementation of the technology requires the development of methods for printing structural elements, taking into account the anisotropy of their properties depending on the printing direction.Conclusions. The reinforcement of structures remains a complex issue in 3D printing technology. To achieve maximum mechanical properties of printed structures, multicriteria optimization is required, taking into account rheological requirements for mixtures, reinforcement peculiarities and due to the arrangement of metal elements and the adhesion strength of layers. The complex optimization of the rheology of concrete mixtures, especially those filled with reinforcing fibres, is supplemented by the factors of time and changing environmental conditions, which are ignored or accepted as insignificant at the current stage of technology development. The application of “smart” materials forms the way for its improvement.